PENGARUSUTAMAAN GENDER DAN OPTIMALISASI PERAN SERIKAT PEKERJA SEBAGAI UPAYA PERLINDUNGAN BERBASIS GENDER BAGI PEREMPUAN BURUH PABRIK DI KABUPATEN KARANGANYAR (Faculty of Social Science, Universitas Negeri Semarang, 2013)
This research aims to find strategies of gender-based protection for women worker in Karanganyar. The emergence of Legal Law (Instruksi Presiden No. 9 Tahun 2000) about gender mainstreaming making every stakeholders should integrate gender as perspective in every policy. One of efforts to protect women worker based on gender perspective could be done by implemented gender mainstreaming. Based on the research, strategy of gender-based protection for women worker could be run through worker union. Every company should have union worker and make contractual worker (PKB). The protection of women worker could be done by integrating gender perspective on contractual worker arrangement. Therefore every department in Karanganyar should implemented gender mainstreaming so monitoring and evaluation could be done by Department of Labor and Transmigration. This department should be ensure that the contractual worker in every company has a specific protection for women worker.